Diversity of Cardiac and Gastrointestinal Presentations of Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19: A Case Series. (February 2021) - Shikhare, Anuja R.; Iqbal, Rimsha M.; Tariq, Rabail; Turner, Daniel R.; Gebara, Bassam M.; Freij, Bishara J.
COVID-19 is generally a benign or asymptomatic infection in children, but can occasionally be severe or fatal. Delayed presentation of COVID-19 with hyperinflammation and multi-organ involvement was recently recognized, designated the Multisystem Inflammatory Syndrome in Children (MIS-C). Six children with MIS-C with molecular and serologic evidence of SARS-CoV-2 infection were admitted to our hospital between May 5, 2020 and June 25, 2020. All had fever and weakness; 4/6 presented with gastrointestinal symptoms. Two children had features of complete Kawasaki disease, 3 had incomplete Kawasaki disease, while 1 had terminal ileitis with delayed onset of circulatory shock. Treatment consisted of intravenous immunoglobulin and aspirin for Kawasaki-like disease. Remdesivir, corticosteroids, and infliximab were used when indicated. Median hospitalization was 7 days. Immediate treatment resulted in rapid clinical improvement. In children presenting with hyperinflammatory syndromes without cardiac manifestations, testing for SARS-CoV-2 RNA and antibodies, with close cardiac monitoring should be pursued due to the manifold presentations of SARS-CoV-2 infection in children.